2006
DOI: 10.1038/nature04555
|View full text |Cite
|
Sign up to set email alerts
|

Winter forest soil respiration controlled by climate and microbial community composition

Abstract: Most terrestrial carbon sequestration at mid-latitudes in the Northern Hemisphere occurs in seasonal, montane forest ecosystems. Winter respiratory carbon dioxide losses from these ecosystems are high, and over half of the carbon assimilated by photosynthesis in the summer can be lost the following winter. The amount of winter carbon dioxide loss is potentially susceptible to changes in the depth of the snowpack; a shallower snowpack has less insulation potential, causing colder soil temperatures and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
334
6
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 492 publications
(394 citation statements)
references
References 30 publications
34
334
6
5
Order By: Relevance
“…We also found that bacterial secondary succession proceeded very rapidly in the postdisturbance landscape, as communities from 4 and 16 weeks postburn were significantly different, not only in terms of the OTUs present, but also with respect to the phyla/ subphyla proportional abundances (Figure 1, Supplementary Figures S1 and S3). Seasonal effects are known to influence soil microbial community abundances and activities (Monson et al, 2006;Schmidt et al, 2007) and, consistent with these observations, we observed a small but significant difference in the bacterial community structure (Figure 1) of unburned samples from 4 (fall) and 16 (winter) weeks. As well, pH and soil moisture were different between the two sampling timepoints (Table 1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We also found that bacterial secondary succession proceeded very rapidly in the postdisturbance landscape, as communities from 4 and 16 weeks postburn were significantly different, not only in terms of the OTUs present, but also with respect to the phyla/ subphyla proportional abundances (Figure 1, Supplementary Figures S1 and S3). Seasonal effects are known to influence soil microbial community abundances and activities (Monson et al, 2006;Schmidt et al, 2007) and, consistent with these observations, we observed a small but significant difference in the bacterial community structure (Figure 1) of unburned samples from 4 (fall) and 16 (winter) weeks. As well, pH and soil moisture were different between the two sampling timepoints (Table 1).…”
Section: Discussionsupporting
confidence: 73%
“…We now possess the tools to reveal high-resolution details about temporal and structural changes in microbial community structure. As microbial community structure drives function, some argue that there is value in knowing 'who does what' to understand and predict ecosystem processes (Zak et al, 2003;Monson et al, 2006;Van Der Heijden et al, 2008). However, as mentioned above, many studies reveal that environmental factors are important determinants of microbial community structure (Fierer and Jackson, 2006;Lozupone and Knight, 2007;Logue and Lindstrom, 2010;Nemergut et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The overwhelming majority of prior studies of CH 4 fluxes in the Arctic have been carried out during the summer months (12)(13)(14)(15). However, the fall, winter, and spring months represent 70-80% of the year in the Arctic and have been shown to have significant emissions of CO 2 (16)(17)(18). The few measurements of CH 4 fluxes in the Arctic that extend into the fall (6,7,9,10) show complex patterns of CH 4 emissions, with a number indicating high fluxes (7,10).…”
mentioning
confidence: 99%
“…This is a serious gap in our general understanding of biodiversity, given that microbes are abundant and diverse, play a central role in ecosystem functioning, and will likely be an important component of ecosystem response to global warming (11)(12)(13). Elevational diversity studies that consider empirical patterns of macroorganisms and microorganisms in parallel are needed to provide a more unified framework for understanding diversity patterns in Earth's major environmental gradients and predicting systemwide ecological responses to climatic change.…”
mentioning
confidence: 99%